Syringe purification with UPLC-MS/MS for detection of antibiotics in tea garden soil after long-term application of manure. Issue 31 (1st August 2022) - Zheng, Binyu; Song, Ningying; Wu, Huizhen; Tong, Jianying; Sun, Nabo
Abstract : The residue of antibiotics in the soil is becoming more and more common, which may affect the normal growth of plants and organisms. Abstract : The residue of antibiotics in the soil is becoming more and more common, which may affect the normal growth of plants and organisms. The aim of this study was to investigate the residues of antibiotics in tea gardens' soil after a long-term application of manure. An ultra-high performance liquid chromatography–tandem mass spectrometry method was developed to simultaneously determine the residues of 32 antibiotics in the soil of tea gardens after fertilization. The samples were extracted with methanol–acetonitrile and purified with C18 at the same time. Then, mixed dispersive sorbents dispersed in a syringe were used for the second purification. The results showed that the antibiotics have a good linear relationship within the range. The recovery rate is 70.1–120.3%. The applicability of the method was demonstrated by analyzing 30 real samples (with a detection rate of 43.3%). The method is a simple and environmentally friendly method for the analysis of multiple antibiotics in soils, and it could provide a basis for the risk assessment of antibiotics in agricultural environments and the standard application of organic fertilizers in tea gardens.